Pseudoaneurysm of Distal Anterior Tibial Artery after Minimally Invasive Percutaneous Plate Osteosynthesis for Distal Tibial Fracture: A Case Report - Karki, Netra Bahadur; Paudel, Sushil; Adhikari, S; Pokharel, Rohit Kumar (Nepal Orthopaedic Association Journal, 2019)
Traumatic pseudoaneurysm of anterior tibial artery is a rare condition after operative intervention of tibial shaft fractures. Few authors have reported proximal anterior tibial artery pseudoaneurysm after intramedullary interlocking nailing and minimally invasive percutaneous osteosynthesis but the incidence of distal anterior tibial artery pseudoaneurysm after minimally invasive percutaneous osteosynthesis is very rare with just one case being reported in literature. We report a case of distal anterior tibial artery pseudoaneurysm after minimally invasive percutaneous osteosynthesis done for distal tibial shaft fracture and discuss its probable cause and management.